Criminal Law Review of Investment Managers Who Implement Pyramid Schemes - F. Martono, Yacob; Setyobowo Sangalang, Rizki; Januardy, Ivans; Ronggo Wicaksono, Restu (Jurnal Ilmu Hukum Tambun Bungai, 2023)
Indonesian people's interest in investment is increasing, this is in line with current technological advances. The number of capital market investors in mid-October 2021 grew by around 68 percent from the end of 2020 which reached 3.88 million people. With advances in technology and the rapid flow of information in cyberspace, many people only think about the benefits to be gained from an investment and have no knowledge or lack of understanding about investments and their risks. This is proven by the large number of people who are victims of an illegal investment that implements schemes, for example in the investment case of capital injection (sunmod) for medical devices, the number of victims is estimated to reach 3,000 people with a loss of Rp. 1.2 Trillion. The schematic diagram is also interpreted as a fake investment system that pays old participants from the money of the new participants they recruit, not from real profits. This scheme is aimed at collapsing, because the revenue if any, will hurt the participants. The illegality of the scheme lies in the incurring of losses at a rate below the loss of the amount of money invested in the business. Investment business activities that apply schemes can be held criminally accountable for violating Law Number 7 of 2014 concerning Explanation of Trade Article 9. Law Number 8 of 1999 concerning Consumer Protection Article 8 paragraph (1) letters a, d, e, f, Article 9 paragraph (1) letters c, e, j, k, Article 10, Article 13 paragraph 1, Article 15, and Article 17 paragraph (1) letters a, b, c, d. Regulation of the Minister of Trade Number 70 of 2019 concerning the Direct Distribution of Goods Article 21 letter k, Law Number 21 of 2008, Article 59. Law of the Republic of Indonesia Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking Article 46. ​​​​Law Number 8 of 1995 concerning Capital Markets Article 103. Article 378 of the Criminal Code concerning fraud.